Meninjau Kembali Peran Strategis Pendidikan Islam di Indonesia - Dewi, Lilis; Sukandar, Ahmad; Fathurrahman, Asep (Lembaga Yasin AlSys, 2023)
People continue to argue about education for years. Both Islamic religious education and the education system in general make people curious. Muslims believe that their education system should be holistic. This means combining spiritual, intellectual, emotional and physical development. It is based on teachings from the Qur'an and Hadith. This is done through qualitative research with a transcendental phenomenological approach. The study seeks to learn more about educators' experiences in helping autistic children learn. Qualitative research, as defined by its name, encourages an understanding of a subject through consideration of perceptions, motivations, behaviors and other aspects that help define it. This is achieved through the use of language and words to describe this experience holistically. . Formal education in Indonesia is in the form of Islamic education at the grassroots level. It is said that this is the first form of formal education in the country, especially at the national level. By fostering a general sense of learning rooted in respect, it is believed to have made a major contribution to Indonesia's current education system. It is clear that Islamic education plays a huge role in Indonesian culture. It is so pervasive throughout the country that students are encouraged to actively participate in public life to shape their character as Muslims and maintain their cultural and religious identity.